Seismic line disturbances affect spatial and temporal patterns of snow accumulation in boreal forests - Maryam Bayatvarkeshi; Scott Ketcheson; Melanie Dickie; Robert Serrouya; William Quinton; Maria Strack (Journal of Hydrology, 2026)

An assessment of carbon dioxide exchanges following vascular plant establishment in a constructed boreal watershed - Nataša Popović; Richard M. Petrone; Maria Strack (Journal of Hydrology, 2026)

Edge effects of linear disturbances on plant functional traits in boreal fens of northern Alberta, Canada - Brooklyn Bolstad; Kellina L. Higgins; Ellie Goud; Maria Strack; Anna Dabros (Forest Ecology and Management, 2025)

Intraspecific trait variability in four geographically widespread peatland plant species in Canada - Rachel A. Kendall; Ellie M. Goud; Scott J. Davidson; Nicole Balliston; Claire Estey; Tasha-Leigh Gauthier; Kimberly Kleinke; Andrew Rutland; Maria Strack (Flora, 2025)

Environmental Conditions Modulate Warming Effects on Plant Litter Decomposition Globally - Sarah Schwieger; Ellen Dorrepaal; Matteo Petit Bon; Vigdis Vandvik; Elizabeth le Roux; Maria Strack; Yan Yang; Susanna Venn; Johan van den Hoogen; Fernando Valiño; Haydn J. D. Thomas; Mariska te Beest; et al. (Ecology Letters, 2025)
Empirical studies worldwide show that warming has variable effects on plant litter decomposition, leaving the overall impact of climate change on decomposition uncertain. We conducted a meta‐analysis of 109 experimental warming studies across seven continents, using natural and standardised plant material, to assess the overarching effect of warming on litter decomposition and identify potential moderating factors. We determined that at least 5.2° of warming is required for a significant increase in decomposition. Overall, warming did not have a significant effect on decomposition at a global scale. However, we found that warming reduced decomposition in warmer, low‐moisture areas, while it slightly increased decomposition in colder regions, although this increase was not significant. This is particularly relevant given the past decade's global warming trend at higher latitudes where a large proportion of terrestrial carbon is stored. Future changes in vegetation towards plants with lower litter quality, which we show were likely to be more sensitive to warming, could increase carbon release and reduce the amount of organic matter building up in the soil. Our findings highlight how the interplay between warming, environmental conditions, and litter characteristics improves predictions of warming's impact on ecosystem processes, emphasising the importance of considering context‐specific factors.

Methane Cycling Microbial Community Characteristics: Comparing Natural, Actively Extracted, Restored and Unrestored Boreal Peatlands - Aneta Bieniada; Laura A. Hug; Christopher T. Parsons; Maria Strack (Wetlands, 2023)

The Potential of Peatlands as Nature-Based Climate Solutions - Maria Strack; Scott J. Davidson; Takashi Hirano; Christian Dunn (Current Climate Change Reports, 2022)

CO2 uptake decreased and CH4 emissions increased in first two years of peatland seismic line restoration - Megan Schmidt; Scott J. Davidson; Maria Strack (Wetlands Ecology and Management, 2022)

Restoration approach influences carbon exchange at in-situ oil sands exploration sites in east-central Alberta - Kimberley R. Murray; Melanie Bird; Maria Strack; Michael Cody; Bin Xu (Wetlands Ecology and Management, 2021)

Methane emissions from fens in Alberta’s boreal region: reference data for functional evaluation of restoration outcomes - Aneta Bienida; Vinay Daté; Roxane Andersen; Felix Nwaishi; Jonathan Price; Md. Sharif Mahmood; Maria Strack (Wetlands Ecology and Management, 2020)

Key Species Superpose the Effect of Species Richness and Species Interaction on Carbon Fluxes in a Restored Minerotrophic Peatland - Golnoush Hassanpour Fard; Elena Farries; Vicky Bérubé; Line Rochefort; Maria Strack (Wetlands, 2020)

Interactive effects of vegetation and water table depth on belowground C and N mobilization and greenhouse gas emissions in a restored peatland - Cristina Lazcano; Anoop S. Deol; Martin E. Brummell; Maria Strack (Plant and Soil, 2020)

Multi‐year net ecosystem carbon balance of a restored peatland reveals a return to carbon sink - Kelly A. Nugent; Ian B. Strachan; Maria Strack; Nigel T. Roulet; Line Rochefort (Global Change Biology, 2018)
Peatlands after drainage and extraction are large sources of carbon (C) to the atmosphere. Restoration, through re‐wetting and revegetation, aims to return the C sink function by re‐establishing conditions similar to that of an undrained peatland. However, the time needed to re‐establish C sequestration is not well constrained due to the lack of multi‐year measurements. We measured over 3 years the net ecosystem exchange of CO 2 ( NEE ), methane ( ), and dissolved organic carbon ( DOC ) at a restored post‐extraction peatland ( RES ) in southeast Canada (restored 14 years prior to the start of the study) and compared our observations to the C balance of an intact reference peatland ( REF ) that has a long‐term continuous flux record and is in the same climate zone. Small but significant differences in winter respiration driven by temperature were mainly responsible for differences in cumulative NEE between years. Low growing season inter‐annual variability was linked to constancy of the initial spring water table position, controlled by the blocked drainage ditches and the presence of water storage structures (bunds and pools). Half‐hour at RES was small except when Typha latifolia ‐invaded drainage ditches were in the tower footprint; this effect at the ecosystem level was small as ditches represent a minor fraction of RES . The restored peatland was an annual sink for CO 2 (−90 ± 18 g C m −2 year −1 ), a source of CH 4 (4.4 ± 0.2 g C m −2 year −1 ), and a source of DOC (6.9 ± 2.2 g C m −2 year −1 ), resulting in mean net ecosystem uptake of 78 ± 17 g C m −2 year −1 . Annual NEE at RES was most similar to wetter, more productive years at REF . Integrating structures to increase water retention, alongside re‐establishing key species, have been effective at re‐establishing the net C sink rate to that of an intact peatland.

Impact of winter roads on boreal peatland carbon exchange - Maria Strack; Divya Softa; Melanie Bird; Bin Xu (Global Change Biology, 2018)
Across Canada's boreal forest, linear disturbances, including cutlines such as seismic lines and roads, crisscross the landscape to facilitate resource exploration and extraction; many of these linear disturbances cross peatland ecosystems. Changes in tree canopy cover and the compression of the peat by heavy equipment alter local thermal, hydrological, and ecological conditions, likely changing carbon exchange on the disturbance, and possibly in the adjacent peatland. We measured bulk density, water table, soil temperature, plant cover, and CO 2 and CH 4 flux along triplicate transects crossing a winter road through a wooded fen near Peace River, Alberta, Canada. Sample plots were located 1, 5, and 10 m from the road on both sides with an additional three plots on the road. Productivity of the overstory trees, when present, was also determined. The winter road had higher bulk density, shallower water table, higher graminoid cover, and thawed earlier than the adjacent peatland. Tree productivity and CO 2 flux varied between the plots, and there was no clear pattern in relation to distance from the road. The plots on the winter road acted as a greater CO 2 sink and greater CH 4 source compared to the adjacent peatland with plots on the winter road emitting on average (standard error) 479 (138) compared to 41 (10) mg CH 4 m −2 day −1 in the adjacent peatland. Considering both gases, global warming potential increased from 70 to 250 g CO 2 e m −2 year −1 in the undisturbed area to 2100 g CO 2 e m −2 year −1 on the winter road. Although carbon fluxes on any given cutline through peatland will vary depending on level of compaction, line width and vegetation community shifts, the large number of linear disturbances in Canada's boreal forest and slow recovery on peatland ecosites suggest they could represent an important anthropogenic greenhouse gas source.

Growing season carbon gas exchange from peatlands used as a source of vegetation donor material for restoration - Kimberley R. Murray; Andrea K. Borkenhagen; David J. Cooper; Maria Strack (Wetlands Ecology and Management, 2017)

Effect of plant functional type on methane dynamics in a restored minerotrophic peatland - Maria Strack; Kisa Mwakanyamale; Golnoush Hassanpour Fard; Melanie Bird; Vicky Bérubé; Line Rochefort (Plant and Soil, 2017)

The role of waterborne carbon in the greenhouse gas balance of drained and re-wetted peatlands - Chris D. Evans; Flo Renou-Wilson; Maria Strack (Aquatic Sciences, 2016)

Methane Flux Influenced by Experimental Water Table Drawdown and Soil Warming in a Dry Boreal Continental Bog - Tariq M. Munir; Maria Strack (Ecosystems, 2014)

Distribution and diversity of V errucomicrobia methanotrophs in geothermal and acidic environments - Christine E. Sharp; Angela V. Smirnova; Jaime M. Graham; Matthew B. Stott; Roshan Khadka; Tim R. Moore; Stephen E. Grasby; Maria Strack; Peter F. Dunfield (Environmental Microbiology, 2014)
Summary Recently, methanotrophic members of the phylum V errucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16 S rRNA gene amplicons. Putative methanotrophic V errucomicrobia were found in samples covering a broad temperature range (22.5–81.6° C ), but only in acidic conditions ( pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16 S rRNA gene sequence clusters of putative methanotrophic V errucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6° C ) grouped with known thermoacidiphilic ‘ M ethylacidiphilum ’ isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1° C ) and a representative mesophilic methanotroph from this group was isolated (strain LP 2 A ). Genome sequencing verified that strain LP 2 A possessed particulate methane monooxygenase, but its 16 S rRNA gene sequence identity to ‘ M ethylacidiphilum infernorum ’ strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic V errucomicrobia . Using pmoA ‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP 2 A ‐like pmoA sequences in the cooler surface layers and ‘ M ethylacidiphilum'‐ like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic V errucomicrobia . However, both were detected only in acidic geothermal environments.

Functional identification and differential expression of 1-deoxy-d-xylulose 5-phosphate synthase in induced terpenoid resin formation of Norway spruce (Picea abies) - Michael A. Phillips; Michael H. Walter; Steven G. Ralph; Paulina Dabrowska; Katrin Luck; Eva Maria Urós; Wilhelm Boland; Dieter Strack; Manuel Rodríguez-Concepción; Jörg Bohlmann; Jonathan Gershenzon (Plant Molecular Biology, 2007)